1980
DOI: 10.3758/bf03199910
|View full text |Cite
|
Sign up to set email alerts
|

A note on a second stage in the formation of illusory contours

Abstract: Figure 1. The Koffka figure with an indefinitely shaped region of enhanced brightness at the center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…It is suggested that "classical" or simultaneous contrast from the corner elements and line-end contrast generated by the ends of the side elements (Day & Jory, 1978;Frisby & Clatworthy, 1975;Kennedy, 1979) spread to the partially delineated borders of the rectangle (or other shapes) in a manner described earlier by Day and Jory (1980). It is suggested also that apparent overlay serves primarily to enhance the delineation of the border with which the illusory contour is coincident, by apparent stratification of the rectangular figure and the corner elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that "classical" or simultaneous contrast from the corner elements and line-end contrast generated by the ends of the side elements (Day & Jory, 1978;Frisby & Clatworthy, 1975;Kennedy, 1979) spread to the partially delineated borders of the rectangle (or other shapes) in a manner described earlier by Day and Jory (1980). It is suggested also that apparent overlay serves primarily to enhance the delineation of the border with which the illusory contour is coincident, by apparent stratification of the rectangular figure and the corner elements.…”
Section: Discussionmentioning
confidence: 99%
“…Second, do the incomplete octagons and the parts of the incomplete cross impinging on the hypothetical edge of the rectangle contribute equally to the formation of the illusory contours? It is conceivable that, as Day and Jory (1980) suggested, the ends of the lines merely determine the location of the contours. The purpose of the first experiment was to answer these two questions.…”
Section: Methodsmentioning
confidence: 99%
“…The illusory surface has no clearly defined boundaries. One may perceive a circle, a diamond, or a square in the center ofthe figure (see also Day & Jory, 1980). In the second stimulus, one perceives a sharp, illusory contour separating the two phase-shifted gratings.…”
Section: IIImentioning
confidence: 99%
“…Monash University, Clayton, Victoria, Australia Day and Jory (1980) and Kasperczyk (1983a, 1983b) have proposed that illusory contours, apparent edges in physically uniform regions (Ehrenstein, 1942;Gregory, 1972;Kanizsa, 1955;Schumann, 1904), are due primarily to the spread of induced contrast to partially delineated borders. Brightness (or darkness) is enhanced by simultaneous and line-end contrast and reduced by assimilation of brightness.…”
Section: R H Daymentioning
confidence: 99%
“…Earlier, Day and Jory (1980) showed that line-end contrast (Day & Jory, 1978;Frisby & Clatworthy, 1975;Kennedy, 1979)generated in a cross-like figure ( Figure 3A) devised by Koffka (1935) be expected to spread to the borders of the same figures. Neon spreading was generated in the Koffka figure by completing the black lines forming the arms of the cross with gray lines, as shown in Figure 3B.…”
mentioning
confidence: 99%